2021
DOI: 10.1111/dar.13395
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and preliminary effectiveness of internet‐mediated ‘relapse prevention therapy’ for patients with alcohol use disorder: A pilot study

Abstract: Introduction. To assess the feasibility, acceptability and preliminary effectiveness of synchronous internet-mediated relapse prevention therapy (i-RPT) in alcohol use disorder. Methods. This was a pilot, quasi-experimental study. Thirty-two adult men with alcohol use disorder were recruited through purposive sampling from an outpatient setting. We assessed patterns of drinking, craving, motivation and coping. Patients received five twice-weekly sessions of i-RPT. They were reassessed 12 weeks post-interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Another recent study also showed the feasibility and effectiveness of telemedicine-delivered cognitive behavior therapy in an Indian setting. [ 14 ] The present study expanded the scope of telemedicine to ACT delivery. Given the potential for scaling up and patients’ convenience in telehealth-based ACT, these findings must be replicated in randomized clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study also showed the feasibility and effectiveness of telemedicine-delivered cognitive behavior therapy in an Indian setting. [ 14 ] The present study expanded the scope of telemedicine to ACT delivery. Given the potential for scaling up and patients’ convenience in telehealth-based ACT, these findings must be replicated in randomized clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…[ 271 272 273 274 ] Computer-delivered and technology-based interventions for AUD and hazardous drinking are of recent interest. [ 275 276 277 278 279 ] The research focused on delivering interventions using trained nursing professionals and community-level counsellors and reported them as feasible and effective. [ 280 281 ]…”
Section: Psychological Interventionsmentioning
confidence: 99%
“…Even among treatment-seekers, alarmingly high relapse rates form a solid rationale for assessing craving as a potential factor for relapse prevention. [ 7 9 ]…”
Section: Introductionmentioning
confidence: 99%